Learning styles: a pedagogical proposal to enhance foreign language teaching in Licenciatura en Lenguas Modernas at Universidad del Quindío (Revista de Investigaciones Universidad del Quindío, 2012)
This article presents the results of the research entitled,“Learning styles: a pedagogical proposal to enhance foreign language teaching in Licenciatura en Lenguas Modernas at Universidad del Quindío.”This research, non-experimental, transversal and exploratory-descriptive, falls within the realm of the theory of learning styles and its application as a teaching tool for the optimization of the processes of teaching and learning of foreign languages. Its purpose was to identify, by applying Felder and Silverman’s and Herrmann’s question-naires, the learning styles of students; and, by applying Herrmann’s questionnaire for teachers, the personal teaching styles of teachers in the basic French and English courses at the Modern Languages Program in Universidad del Quindío. The diagnosis confirmed the heterogeneity of students’ learning styles and the dissi-milarity between these styles and the teachers’ personal teaching styles. This research provides, as a product, some pedagogical guidelines for the future structuring of a pedagogical proposal of didactic sequences that might enhance teaching and learning in this field of study and might eventually be of use in curriculum design, based on the implications of the learning and teaching styles detected.
Keywords: Learning styles; teaching styles; learning; pedagogical proposal; curriculum design